Development of method for determining glyphosate residues in palm oil matrices and soil samples using high performance liquid chromatography - Mohd Saleh, Mohamad Fariq Fitri (2015)
Herbicides such as glyphosate is commonly used in palm oil plantation to control broad-leaved weeds and grass which can result in loss of yield. The use of pesticides in oil palm plantations has resulted in the growing concern of the presence and danger of the residues in the palm oil as well as in the environment. Glyphosate is one of the common herbicides use to control weeds in the plantation and of concern of its residue in palm oil. Thus, a method was developed in order to monitor its leaching and persistence in oil palm agroenvironment. Although a lot of researches on pesticide residue determination in oil palm matrices had been carried out, the analytical methods for determining the residue of glyphosate in palm oil matrices via pre-column derivatization with FMOC-Cl have limited reports. The use of pre-column derivatization provides numerous advantages in terms of the use of non-complicated instruments, rapid, fewer restrictions, and efficient. The detection and quantification of glyphosate was comprehensively studied by using High Performance Liquid Chromatography with Fluorescence Detector (HPLC-FLD).The instrumentation parameters such as detector wavelength, flow rate of mobile phase, selection of mobile phase was optimized. In the analysis to determine residues of glyphosate in palm oil samples, extraction step based on liquid-liquid extraction (LLE) technique with precolumn derivatization was optimized. Dichloromethane and water were used as the extraction solvent and centrifuged for 30 minute at 3000 rpm. The extraction of glyphosate from soil samples was also investigated and agitation with magnetic stirrer was chosen as the optimized extraction technique. Extraction parameters such as extraction solvent (deionized water, sodium hydroxide and potassium dehydrogen phosphate), solvent volume (15, 25 and 30 mL), and duration of extraction (30,45 and 60 min) were comprehensively investigated and optimized. The optimized conditions were obtained using 25 mL of potassium dehydrogen phosphate as the extraction solvent and 30 min as the duration of extraction. Recovery of glyphosate obtained from spiked crude palm oil (CPO), crude palm kernel oil (CPKO), soil samples were 85-97,87-92 and 83-88%, respectively with relative standard deviations of less than 3%. The limit of detection (LOD) and limit of quantification, (LOQ) for glyphosate in spiked CPO, CPKO and soil samples was 0.01 and 0.05 μg/mL, respectively. Validation studies were also carried out and the method developed for analysis of glyphosate in spiked CPO, CPKO and soil samples gave the best reproducibility with low % RSD for all tested matrices.